THE MAXIM APPLICATION'S CUSTOMER SATISFACTION LEVEL AND THE IMPACT OF SERVICE QUALITY AND COSTS - Himawan; Yusnanto, Tri (Journal of Information Systems Management and Digital Business, 2023)
The determining factors of customer satisfaction include service quality and price. This study aims to determine whether there is a significant influence of Service Quality and Price on customer satisfaction on Maxim online motorcycle taxi application in Palembang. The research data was obtained by distributing questionnaires to respondents. The population and sample in this study were 54 respondents. This study uses the Service Quality method which contains tangible, reliability, responsiveness, assurance and empathy variables. Data analysis in this study used variable instrument tests and questionnaire value analysis from respondents. The results of the analysis in this study show that the Empathy variable has the most significant influence value on the customer satisfaction variable.